Chrysanthine theoretical thought and notation system-The relation between Orality and Textuality - Andrikos, Nikos (Epistēmēs Metron Logos, 2021)
Two centuries after the release of Chrysanthos’ Εισαγωγή εις το Θεωρητικόν και Πρακτικόν της Εκκλησιαστικής Μουσικής, this treatise remains one of the most important sources of theoretical thought in the field of Greek Orthodox Ecclesiastical Music. Moreover, it is widely known that the theoretical essays of Chrysanthos played a catalytic role regarding the structure of the modal system of Octaechia, the formulation of the new Parasemantiki notation, as well as contemporary performance practices. Indeed, Chrysanthos’ contribution to the reformation of the notation system as well as the way he attributed the theoretical content of Ecclesiastical Music, influenced the entire theoretical thought that was produced, at least until the last decades of the 19th century[1]. Therefore, despite individual disagreements that were expressed within the psaltic milieu of the 19th century[2], almost all of the theoreticians who succeeded Chrysanthos based their thought on his fundamental principles. Thus, it is worth mentioning that in treatises that followed the Reform of 1814, repetitions are frequently detected, even of Chrysanthos’ points that could be considered as scientifically problematic[3]. [1] See Νίκος Ανδρίκος, Η Εκκλησιαστική μουσική της Σμύρνης (1800-1922), (2015), 124. [2] About this issue, see Αντώνιος Χατζόπουλος, Η εκκλησιαστική μουσική παιδεία στην εκκλησία της Κωνσταντινουπόλεως κατά το 19ο και 20ό αιώνα, (2000); Αχιλλεύς Χαλδαιάκης, “Η διδασκαλία της Ψαλτικής Τέχνης: Παρελθόν, παρόν και μέλλον”, Βυζαντινομουσικολογικά, Τόμος Α΄, Θεωρία, (2014), 50-52. [3] Among others, the most indicative example was the repetition of Chrysanthos’ misguided calculation-measurement of the basic scale’s size. This issue became the reason of a wide discourse between important theoreticians of the 19th century through the daily and periodical press and led to the convocation of the Music Committee of 1881. See Ανδρίκος, 135-145.